Filipino philosophy, western tradition, and nation building - Gripaldo, Rolando M. (Animo Repository, 2007)
In this paper, the author (1) makes the distinctions between traditional and cultural approaches to philosophy and between philosophers and scholars of philosophy, (2) explains why the Filipino philosophy that developed is Western in orientation, (3) discusses the problems of philosophy in the Philippines, (4) argues for the relevant linkage of philosophy to nation building and, among others, (5) enumerates some principles that help guide the author in developing philosophy in the Philippines.